OSCE in Internal Medicine for Undergraduate Students Newly Encountered with Clinical Training - Hani Almoallim (Association of American Medical Colleges, 2006)
Abstract This resource is an objective structured clinical examination (OSCE) designed for fourth-year medical students. The aim of this exam is to assess the bedside skills of students in history taking and physical examination. Checklists were designed for eight history stations and 15 physical exam stations in internal medicine. Every expected action from students was put in these checklists with a corresponding mark. The examiner has to indicate either true, prompted, or false for each action based on the performance of the student. Note that the term "prompted" should be ticked when a student needed a hint or a clue to answer correctly. There is a space for comments on each action. Each student should be examined in five stations; three physical exam and two history taking. Each station is 10 minutes long. The exam is designed in blocks with three examiners for each block. Some examiners may not stick to the checklist and go beyond. They have to understand that this is prohibited. Some mark distribution was adjusted based on comments from examiners. The guidelines should be distributed in the first day of the course. A special meeting with all examiners should be arranged and a comprehensive description of the exam and how to use the checklists should be done. This preferably should be conducted a day or two before the exam. It is recommended to have a special computer program for immediate scoring of the results. A minimum of two persons should be available to help in organizing the flow of students during the examination.